Pandangan Dunia Pengarang Terhadap Gender dalam Anime Kimi No Na Wa Karya Makoto Shinkai - Apriliani, Ni Luh; Anggraeny, Renny (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2022)
The title of this research is “The Author’s World View of Gender in Anime Kimi no Na wa by Makoto Shinkai. The aim of this research is to determine the author’s world view of gender in Anime Kimi no Na wa by Makoto Shinkai. The observation method and note-taking technique used in data collection. The theory used in this research is theory of genetic structuralism and theory of author's world view from Goldmann. The author's world view on gender is illustrated through three social problems, namely 1) gender subordination: women have the right to develop themselves; 2) gender stereotypes: societal stereotypes are subjective; 3) gender violence: the importance of respecting the position of women. The author wants to convey the message that gender is something that can be exchanged, so that it requires equal treatment of everyone regardless of their sex.